Scientometric Review 1974-2024: The Evolution of Linguistic and AI Collaboration - Okta, Setyo Luthfi; Putra, Deva (Communication In Research And Publications, 2025)
Since 1974, the collaboration between linguistics and artificial intelligence (AI) has evolved from a conceptual approach to a well-established interdisciplinary synergy. This study aims to scientometrically evaluate the dynamics and development directions of linguistics–AI research over the past five decades, by analyzing 5,750 articles indexed in the Web of Science. The results show an exponential increase in the number of publications since 2000, with a significant spike post-2018 due to the advancement of deep learning models. Through keyword mapping using VOSviewer and word cloud analysis, five main clusters were identified: Natural Language Processing, Deep Learning, Generative Language Models (including ChatGPT), Computational Linguistics, and Educational Applications. In addition, countries such as China, the United States, and Italy are listed as major contributors, with institutions such as Tsinghua University and MIT being the most productive centers of research activity. The discussion shows that AI has transformed from a tool to a collaborative partner in linguistic practice, education, and scientific writing. However, ethical challenges such as algorithmic bias and underrepresentation of minority languages ​​remain major concerns. This study emphasizes the importance of a critical and inclusive approach so that linguistic collaboration is not only technological, but also humanistic. The findings provide a comprehensive picture of the evolution, potential, and challenges of linguistic collaboration, and open new directions for future research.